2012
DOI: 10.1002/fam.2152
|View full text |Cite
|
Sign up to set email alerts
|

Study of children evacuation from pre‐school education institutions

Abstract: This paper deals with research into the evacuation of children from pre‐school educational institutions. The research was designed to determine possible values for their pre‐movement time and to thoroughly investigate the parameters of their movement along the emergency escape routes. All the stages of the research conducted are described including the preparation and arrangements for the actual observation studies and the collection of basic empirical data and their statistical treatment. This includes the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 4 publications
1
39
0
Order By: Relevance
“…A strong influence of density‐indicated decrease of individual velocity is reported. Results from an evacuation study with preschool participants were reported by Kholshevnikov et al This study was designed as an extension of the empirical database of Predtechenskii and Milinskii . Another publication by Kholshevnikov et al reports findings from evacuation studies of elderly occupants at a senior citizen health care building.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong influence of density‐indicated decrease of individual velocity is reported. Results from an evacuation study with preschool participants were reported by Kholshevnikov et al This study was designed as an extension of the empirical database of Predtechenskii and Milinskii . Another publication by Kholshevnikov et al reports findings from evacuation studies of elderly occupants at a senior citizen health care building.…”
Section: Resultsmentioning
confidence: 99%
“…Velocity-density (top) and flow-density relationship (bottom) of pedestrian movement through a bottleneck considering pedestrians with disabilities compared with the frequently referenced fundamental diagrams by previous studies[10][11][12]113 (with f = 0.113 m 2 ). Empirical data are collected from publications by previous studies 32,78,83,98,[105][106][107][108]110. Data picked up with Web plot digitaliser by the authors from publication.…”
mentioning
confidence: 99%
“…22,23 Egress drills have provided a convenient field laboratory for evacuation researchers, especially during the formative years of the field, above and beyond their original purpose of enhancing life safety. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] This research involved the observation of routine and modified drills performed to satisfy research objectives significantly beyond those of the regulatory requirements-collecting data on specific elements of evacuee performance (eg, pre-evacuation times [24][25][26] and travel speeds [27][28][29][30] ), to assess the evacuation of different occupancy types (eg, apartment blocks, 31,32 hospitals, 33 and schools/universities, 25,34 ), and to examine the impact of different procedural elements (notification type, 35 actions of staff, 33,36 etc), amongst many other factors that might influence performance (eg, culture 34,37 and firefighter activities 28,38 ).…”
Section: What Do We Know About Egress Drills?mentioning
confidence: 99%
“…Koo et al 5 studied how seriously residents with disabilities affect the evacuation of other residents in a high-rise building environment through an agent-based model. Kholshchevnikov et al 6 investigated the evacuation of children from pre-school educational institutions. Pre-movement time and the relationships between density and speed during upward and downward movement were analyzed for children.…”
Section: Introductionmentioning
confidence: 99%